Design and fabrication of road footpath cleaner machine / Abdul Fattah Zuhair Zukri and Haszeme Abu Kasim - Zukri, Abdul Fattah Zuhair; Abu Kasim, Haszeme (School of Mechanical Engineering, 2023)
The aim of this project is to develop a sweeping machine that is both eco-friendly and versatile enough to clean small and large areas. Currently, road cleaning is done manually, which puts workers at risk of health problems like asthma and skin irritation. The proposed eco-friendly sweeper machine is cost-effective, efficient, and easy to use, making it ideal for cleaning both large and small spaces. Additionally, it is designed to avoid the use of electricity and diesel engines, which would eliminate the risk of pollution, including noise and air pollution. Ultimately, this machine offers a practical and eco-conscious solution for maintaining clean and safe environments